Gerçek kişi tacir - Kuru, Özge (My University, 2015)
Türk Ticaret Kanunu, ticari işletme kavramını temel almakla birlikte kanunda tacir kavramına da yer verilmiş ve tacir sıfatına sahip olmaya önemli sonuçlar bağlanmıştır. Öte yandan, ticaret hukukunda, kişiler hukukundaki gerçek ve tüzel kişi ayrımına paralel biçimde gerçek ve tüzel kişi tacir ayrımı yapılmıştır. Başlıca örneği ticaret şirketleri olan tüzel kişi tacirler araştırmamızın kapsamı dışındadır. Gerçek kişi tacir, TTK. 12/ 1’de, bir ticari işletmeyi kısmen de olsa kendi adına işleten kişi olarak tanımlanmıştır. Gerçek kişilerde tacir sıfatının kazanılması için, kanunun sistematiğine uygun olarak, öncelikle bir ticari işletmenin varlığını gerekmektedir. Tacir tanımı da ticari işletme kavramı üzerinden yapılmıştır. Bu bakımdan, hangi durumlarda bir ticari işletme mevcut olduğunun tespiti de önem arzeder. Ticari işletme kavramı ise TTK. 11/ 1’de tanımlanmıştır. Bu düzenlemeye göre, ticari işletme, esnaf işletmesi için öngörülen sınırı aşan düzeyde gelir sağlamayı hedef tutan faaliyetlerin devamlı ve bağımsız şekilde yürütüldüğü işletmedir. Burada tacir işletmesi - esnaf işletmesi arasındaki farklılık ve her iki işletmenin ne şekilde birbirinden ayrılacağı meselesi önem arzeder. Ticari işeletmenin varlığının yanısıra, ticari işletmenin işletilmesi ve işletme faaliyetinin kısmen de olsa kendi adına olması tacir sıfatının tanımsal unsurlarıdır. Gerçek kişi tacir, kanunda öngörülen tacir olmanın sonuçlarına tabi olacaktır. Örnek olarak, gerçek kişi tacir, iflasa tabi olma, ticaret unvanı seçme ve kullanmak, işletmesini ticaret siciline kaydettirmek, ticari defter tutma, ticaret ve sanayi odalarına kaydolmak gibi yükümlülüklere sahip olacaktır. Bir hukuki ilişkinin her iki tarafının tacir olması halinde, örnek olarak kanuni ihtar ve ihbar şekillerine uyma, fatura verme zorunluluğu vb. önemli sonuçlar da doğacaktır.

However Turkish Commercial Code based on the concept of commercial enterprise, also a significant place is given to and bound to have important consequences for the concept of merchant. On the other hand, in commercial law, parallel to the classification of real persons and legal persons in civil law of persons, there is distinction between the real person and legal person merchants. The legal person merchants, which are business companies as main examples are out of scope of our research. Real person merchant is defined in TCC. 12/ 1 as a person who operates a commercial enterprise wholly or partly under his own name. For the acquisition of the title or real person merchant, according to the systematic of commercial code, the existence of a commercial enterprise is primarily required. The definition of real person merchant is made through the concept of commercial enterprise. In this regard, to determinate in which situation there ise a commercial enterprise is also important. The concept of commercial enterprise is defined in TCC. 11/ 1. According to this regulation, commercial enterprises are independent permanent organizations of aiming profit which have financial capacity in amount furthermore than the capital of tradesman enterprises. The difference between commercial enterprise and tradesman enterprise and the problem of seperating two of these enterprises is important here. In addition to the presence of commercial enterprise, the operation of commercial enterprises and operating the business activities at least partly or wholly under his own name are definitional elements of the concept of real person merchant. Real person merchants, who will be the subject to the results of being merchant, which are prescribed by law. For example, the real person merchant will have obligations as to be bound to bankruptcy, selecting and using a trade name, to register the company into the commercial register, commercial bookkeeping, to sign up to commercial and industrial chambers. In case of there being merchants on both sides of a legal relationship, there will be significant consequenses as to comply with the statutory forms of informing and notice, giving invoices, etc.
Keywords: Ticaret hukuku